Marianson : From "Mackinac And Lake Stories", 1899 - Catherwood, Mary Hartwell, 1847-1902 (Salt Lake City, UT : Project Gutenberg, 2007)
"Marianson" by Mary Hartwell Catherwood is a historical novel written during the late 19th century. Set against the backdrop of the War of 1812, the story explores themes of love, sacrifice, and the human spirit amidst the turmoil of conflict. The narrative primarily revolves around the encounters between a young Canadian voyageur and a widow living on Mackinac Island as they navigate the dangers presented by the British and Native American alliances. The plot begins with the British landing on Mackinac Island, where a young voyageur, disillusioned by his role in the conflict, flees to a cave to evade capture. Inside the cave, he meets Marianson Bruelle, a widow who maintains a fiercely independent spirit and has a deep connection to her environment. As they share food and shelter, a bond of intimacy develops between them, culminating in a poignant embrace before the voyageur must leave. However, tragedy strikes when the young man is killed by a Sioux, leaving Marianson devastated. The narrative captures a moment in time where love emerges in the face of impending danger, and ends on a haunting note with Marianson grieving in solitude, holding the lifeless body of her beloved against the backdrop of the vibrant natural landscape they inhabited. (This is an automatically generated summary.)
Release date is 2007-10-30
Produced by David Widger
Keywords: United States -- Social life and customs -- Fiction; Mackinac Island (Mich. : Island) -- Fiction; Michigan -- Fiction